2015
DOI: 10.1210/jc.2015-1779
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Dysglycemia in Pregnant Oklahoma American Indian Women

Abstract: Dysglycemia at some point during pregnancy was common among American Indian women. It was associated with features of insulin resistance and may confer long-term health risks for mother and child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…One of the key features in our study was that we examined whether GDM recurrence was related to lipid profiles. It is of interest to mention that the first-trimester triglyceride concentration in subsequent pregnancy was significantly higher in the group with GDM recurrence, which agrees with the predictive value of the GDM occurrence [28] and progression to diabetes after GDM [29]. The triglyceride level was positively associated with the area under the postpartum glucose curve in women with prior GDM according to clinical research studies [30, 31].…”
Section: Discussionsupporting
confidence: 53%
“…One of the key features in our study was that we examined whether GDM recurrence was related to lipid profiles. It is of interest to mention that the first-trimester triglyceride concentration in subsequent pregnancy was significantly higher in the group with GDM recurrence, which agrees with the predictive value of the GDM occurrence [28] and progression to diabetes after GDM [29]. The triglyceride level was positively associated with the area under the postpartum glucose curve in women with prior GDM according to clinical research studies [30, 31].…”
Section: Discussionsupporting
confidence: 53%
“…A study from Trichy [ 52 ] recently reported GDM prevalence of 13.9 % in first trimester. Data from Oklahoma shows that among American Indians, prevalence of GDM and overt diabetes in first trimester was 24 % and 0.4 % respectively [ 53 ]. There is insufficient data from India on the prevalence of overt diabetes in the first trimester and hence the findings from this study are significant.…”
Section: Discussionmentioning
confidence: 99%
“…Until sample sizes in available pregnancy cohorts with genetic information grow substantially, our collective ability to classify women with GDM via genetic approaches will be limited by our ignorance around genetic variants that influence glycemic physiology and diabetes risk in pregnancy. In addition, continued lack of ethnic diversity in genetic studies will limit the generalizability of such approaches to racial and ethnic minority women who are most likely to benefit, given the higher prevalence of GDM in Asian, Native American, and Latina women (68)(69)(70)(71).…”
Section: Maternal Genotype-based Approaches To Heterogeneity In Gdmmentioning
confidence: 99%